The colour, light, and contrast manual : designing and managing inclusive built environments - Bright, Keith; Cook, Geoff [ (Geoff K.)] (Wiley-Blackwell, 2010)
The design and provision of colour, contrast and lighting in environments is critical in determining how people interact with their environment, and how confident, safe, and secure they will feel when doing so